CHARACTERISTIC OF PHYSICOCHEMICAL AND SENSORY CASSAVA STICK WITH THE SUBSTITUTION OF FERMENTED CASSAVA BAGASSE FLOUR - Zukryandry Zukryandry; Beni Hidayat; Shintawati Shintawati (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Part of the cassava that can be used as a food product is usually starch and and the waste is cassava bagasse. Fermented cassava bagasse flour is a modified semi-solid fermentation product using yeast Saccharomyces cerevisiae which has almost the same quality as modified cassava flour (mocaf), but fermented cassava bagasse flour has advantages compared to mocaf flour, namely high protein content and cheaper production costs. Fermented cassava bagasse flour has various functions which can be used as raw material for the manufacture of various processed products, one of which is cassava stick. The research objective was to see the formulation of fermented cassava bagasse flour to the sensory characteristics of the resulting cassava stick. The study was conducted using a completely randomized design (CRD) including 5 treatment methods, namely cassava starch substituted by fermented cassava bagasse flour 5% (B1), 10% (B2), 15% (B3), 20% (B4) and 25% (B5), each treatment was repeated 3 times. Based on the sensory results, it was obtained that 15% (B3) fermented cassava bagasse flour substitution treatment was the best choice of cassava stick product by panelists. The results of the analysis of cassava stick products were hardness test 3,77 µ (kg / cm2) ; swelling ratio 18,33% ; moisture content 2,20% ; ash content 0,14% ; protein content 10,00% ; fat content 21,00% ; fiber content 0,17%; carbohydrate content 66,49% and total dietary fiber 21,24%.